Post-translational Modifications of the CARMA1-BCL10-MALT1 Complex in Lymphocytes and Activated B-Cell Like Subtype of Diffuse Large B-Cell Lymphoma - Thys, An; Douanne, Tiphaine; Bidère, Nicolas (Frontiers in Oncology, 2018)
Piracy of the NF-kB transcription factors signaling pathway, to sustain its activity, is a mechanism often deployed in B-cell lymphoma to promote unlimited growth and survival. The aggressive activated B-cell like (ABC) subtype of diffuse large B-cell lymphoma (DLBCL) exploits a multi-protein complex of CARMA1, BCL10 and MALT1 (CBM complex), which normally conveys NF-kB signaling upon antigen receptors engagement. Once assembled, the CBM also unleashes MALT1 protease activity to finely tune the immune response. As a result, ABC DLBCL tumors develop a profound addiction to NF-kB and to MALT1 enzyme, leaving open a breach for therapeutics. However, the pleiotropic nature of NF-kB jeopardizes the success of its targeting and urges us to develop new strategies. In this review, we discuss how post-translational modifications, such as phosphorylation and ubiquitination of the CBM components, as well as, MALT1 proteolytic activity, shape the CBM activity in lymphocytes and ABC DLBCL, and may provide new avenues to restore vulnerability in lymphoma.